O impacto das ações promovidas por ONGs socioambientais na cidade de São Paulo - Tavares, Alberto Corunha (2022)
This dissertation approaches urban agriculture as a form of activism and the perpetuation of this practice in the urban peripheral environment. As an example, socio-environmental actions carried out during the pandemic period by an organized and independent movement called the Ato Verde project were used. The aggressive process of urbanization in the city of São Paulo has always prioritized the interests of the market, disregarding urban and housing planning in regions further away from the center. Based on concepts about the urban and the history of the city, a brief chronology of public policies that stimulated “urban” or “community gardens” in recent decades was made. In view of the political and economic scenario, a theoretical basis and participatory observant methodology were sought, acting directly in the planning and execution of the built gardens, in order to demonstrate their transformative potential, especially in communities, either through the transformation of degraded spaces, or in the production and distribution of organic food free of charge to community residents